A procedure for quantification of precipitate microstructures from three-dimensional atom probe data. - Vaumousse, D; Cerezo, A; Warren, P (2003)
New analysis software for selecting and quantifying particles in three-dimensional atom maps has been designed. The selection of solute-rich regions is performed by connecting solute atoms which lie within a fixed distance (d), and taking clusters above a certain minimum number of solute atoms (N(min)). Other atoms within some distance L greater than d are taken to belong to the cluster. However, this results in the inclusion of a shell of matrix atoms, which must be removed through an erosion step, to define the final cluster. Data filtered in this way can be used for subsequent quantification of parameters such as size, shape, composition, number density and volume fraction with better accuracy than by manual selection. The choice of d, N(min) and L values is discussed and some methods of evaluation of these parameters are proposed. Examples are presented on the application of this new software to the analysis of early stage clustering in an Al-Mg-Si-Cu alloy and a copper-containing steel.